Accounting Information Systems and Bank Services: A Study on Their Relationships - Hakim, Md. Abdul (Asian Accounting and Auditing Advancement, 2019)
The bank is one of the emerging sectors of global business where accounting information systems are used significantly in this sector to maintain and monitor the daily bank’s activities. This study is descriptive in nature and done on the basis of the primary data where secondary data is also used. The data are being collected from five selected commercial banks and 100 employees are surveyed as respondents for analyzing and interpreting the perceptions of the employees concerning the role and contribution of AIS towards the bank business in Bangladesh. This study investigates and examines the role of AIS in the bank business. The study also reveals the influential forces of AIS that strongly contributed to the bank sector. Moreover, the relationships between the role of accounting information systems and the optimum bank services in Bangladesh are tested using the surveyed data. The outcome of this present study may help the concerned to develop and maintain principles and policies of AIS regarding the bank services-related activities.